Beam Deflection under Static Loading: Comparison Between Dial Gauge and Total Station Measurements (University of Khartoum Engineering Journal, 2022)
This paper presents the results of experimental findings for beam deflection measurements under static loading using dial gauges and a reflector-less Total Station. The ultimate objective of this work is to compare the performance of the Total Station with respect to the Dial Gauge (DG). Cement bags were utilized for loading test.These loads are accumulated evenly in six steps. The total tested load was 4.2 tons. The tested beams were located in the Sport City-Khartoum State. This work reveals that the reflector-less Total Station-Leica 1202 (RLTS) produces a very strong correlation and an acceptable accuracy that stands within the limits of its minimum decimalfraction of the metric units. Several tests were carried out to confirm the linearity of the deflections against the loads. These tests are very important since they convey the information about the elastic behavior of the tested beams. In this regards, both measuring techniques produce correlation factors and R2 values for the loads vs. thedeflections of more than 0.98. The deflection accuracy of the Total Station, in terms of root-mean-square-error (RMSE), for the three beams were:  0.30 mm,  0.36 mm, and  0.39 mm, respectively. This finding indicates that the Total Station can provide sub-millimeter accuracy with respect to the dial gauge. The maximum deflection was found in beam number 3, which amounts to 7.9 mm from the Total Station and 7.85 mm from the dial gauge. Both measurement techniques produce recovery percentages that were greater than 88%. The overall findings of this experiment indicates that this reflector-less Total Station can be used for on-site measurement of deflection and for awide range of deflection/deformation measurement applications.